Comparative analysis of ZnO-catalyzed photo-oxidation of p-chlorophenols - Gaya, Umar Ibrahim (European Journal of Chemistry, 2011)
The present study compares for the first time the photocatalytic oxidation of three p-chlorophenols (4-chlorophenol, 2,4-dichlorophenol and 2,4,6-trichlorophenol) in irradiated ZnO suspensions. The effect of operating parameters such as catalyst and concentration doses on the decomposition rate of these p-chlorinated compounds has been studied and optimized. The optimal feed concentration for each of the chlorinated phenolic compounds is 50 mg/L whereas the ZnO doses decreased as the number of chlorine substituent is increased. Kinetic profiles on the decomposition of chlorophenols over ZnO agreed with the pseudo-zeroeth order rate scheme with rate constants following the order 2,4,6-trichlorophenol > 2,4-dichlorophenol > 4-chlorophenol. The validity of the pseudo zero order model could be linked to the initial doses of the chlorophenols used vis-à-vis the catalyst. The study revealed stable intermediates of photocatalytic chlorophenol transformation by high performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS) technique. A combined mechanism is given to account for the photocatalytic destruction of the chlorophenols.